2012
DOI: 10.1371/journal.pone.0039958
|View full text |Cite
|
Sign up to set email alerts
|

Management of Symptomatic Sacral Perineural Cysts

Abstract: BackgroundThere has been no consensus on the optimal treatment of symptomatic sacral perineural cysts. Most previous reports concerning the management methods were either sporadic case reports or a series of limited cases. This study is to further optimize the management for patients with symptomatic sacral perineural cysts by analyzing the outcomes of a cohort of patients who were treated with different strategies.Methods and FindingsWe reviewed the outcomes of 15 patients with symptomatic sacral perineural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…When cysts without involved nerve roots fibers are identified under the microscope, use of fibrin glue to seal the fistula may be considered. Xu et al [21] reported favorable results after microsurgical cyst fenestration and imbrication.…”
Section: Discussionmentioning
confidence: 99%
“…When cysts without involved nerve roots fibers are identified under the microscope, use of fibrin glue to seal the fistula may be considered. Xu et al [21] reported favorable results after microsurgical cyst fenestration and imbrication.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al followed two patients who chose not to undergo surgical treatment for 4 years. During this follow up period, their cysts grew significantly and their symptoms worsened [32].…”
Section: Natural Coursementioning
confidence: 81%
“…Additional evidence of increased intraspinal pressure indicates a higher risk of experiencing a dural leak while performing surgery for STCs [6,11,19,25,31,32]. This is because of the fragility of the tissues and the elevated pressure in the spinal canal [10].…”
Section: Pathogenesismentioning
confidence: 99%
“…Mitra et al reported that intralaminar epidural steroid injection provided symptomatic relief in a single patient who experienced radiculopathy caused by a perineural cyst 25. Whereas, Xu et al reported poor outcomes in two patients treated with medication and physical therapy for symptomatic sacral perineural cysts 26. Both patients’ symptoms worsened with time, and MRI revealed that the culpable cysts had increased in size within 5 years of initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%